Pendekatan Inbound Marketing B2B: Analisis Thought Leadership Content Dan Reputasi Korporat Terhadap Keputusan Pemilihan Agensi Iklan PT Larisa Nikko Indonesia - Yeyen Permana; Adinda Amalia Salsabila; Dian Lestari Novianti; Rifkhan Rifkhan (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study examines the effect of Thought Leadership Content and Corporate Reputation on the Advertising Agency Selection Decision of PT Larisa Nikko Indonesia through a Business-to-Business (B2B) Inbound Marketing approach. Advertising agencies increasingly need to build market appeal through content that reflects industry expertise, alongside maintaining corporate reputation as the basis of trust for prospective corporate clients. This study employed a quantitative method with an associative approach. The population consisted of marketing representatives (persons in charge) of client companies that had used or evaluated the services of PT Larisa Nikko Indonesia, with a sample of 100 respondents selected through purposive sampling. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, correlation analysis, the coefficient of determination, t-tests, and F-tests. The results show that Thought Leadership Content partially has a positive and significant effect on the Advertising Agency Selection Decision (B = 0.375; t = 12.909; p = 0.000), and Corporate Reputation also partially has a positive and significant effect (B = 0.294; t = 8.359; p = 0.000). Simultaneously, Thought Leadership Content and Corporate Reputation have a positive and significant effect on the Advertising Agency Selection Decision, with the regression equation Y = 9.429 + 0.375X1 + 0.294X2, an F-value of 304.700 (p = 0.000), and an Adjusted R² of 0.860, meaning both variables jointly explain 86.0% of the variance in the Advertising Agency Selection Decision. These findings confirm that a B2B inbound marketing strategy combining consistent thought leadership content with strong corporate reputation management can effectively increase client companies' tendency to select PT Larisa Nikko Indonesia as their advertising agency.